Mental Health Impact on Caretakers of Children with Neurodevelopmental Disorders in Nepal - Kunwar, Dipak; Shrestha, Barsha; Risal, Ajay (Journal of College of Medical Sciences-Nepal, 2025)
Background The impact of neurodevelopmental disorders (NDD) on the mental well-being and overall quality of life for families with affected children is becoming increasingly recognized. The aim of the study is to see mental health impact on caretakers of children with neurodevelopmental disorder. Methods This hospital based cross-sectional study was conducted in all patients who came to the hospital during three-month period at out patient’s clinic of Department of Psychiatry from August to October 2024. The DASS-21 was employed for the assessment of depression, anxiety and stress. DASS has been translated into various languages, including the presently employed Nepali version. The association between psychosocial and sociodemographic characteristics were assessed using Chi-square test. All statistical analyses were performed using the SPSS version 16 and p-value <0.05 was considered as statistically significant. Results The mean age of caretaker were 45 years. Minor difference was noticed in the number of caretaker belonging to nuclear 28 (59.6%) and joint families 19 (40.4%). Among the caretakers majority were educated 32 (68%), Hindu by religion 31 (66%) and were from urban area 29 (61%). In our sample, we found high level of burden; 42.6% of caretakers had depression, 55.3% had anxiety and 33% had stress. Conclusions Caretakers of children with neuro developmental disorders are more prone to develop high level of burden, depression, anxiety and stress.